Simplest Monodentate Imidazole Stabilization of the oxy‐Tyrosinase Cu2O2 Core: Phenolate Hydroxylation through a CuIII Intermediate. Issue 35 (21st July 2016) - Chiang, Linus; Keown, William; Citek, Cooper; Wasinger, Erik C.; Stack, T. Daniel P.
Abstract: Tyrosinases are ubiquitous binuclear copper enzymes that oxygenate to Cu II 2 O2 cores bonded by three histidine Nτ‐imidazoles per Cu center. Synthetic monodentate imidazole‐bonded Cu II 2 O2 species self‐assemble in a near quantitative manner at −125 °C, but Nπ‐ligation has been required. Herein, we disclose the syntheses and reactivity of three Nτ‐imidazole bonded Cu II 2 O2 species at solution temperatures of −145 °C, which was achieved using a eutectic mixture of THF and 2‐MeTHF. The addition of anionic phenolates affords a Cu III 2 O2 species, where the bonded phenolates hydroxylate to catecholates in high yields. Similar Cu III 2 O2 intermediates are not observed using Nπ‐bonded Cu II 2 O2 species, hinting that Nτ‐imidazole ligation, conserved in all characterized Ty, has functional advantage beyond active‐site flexibility. Substrate accessibility to the oxygenated Cu2 O2 core and stabilization of a high oxidation state of the copper centers are suggested from these minimalistic models. Abstract : Cold copper cores : Three Nτ‐imidazole‐bonded Cu II 2 O2 species were synthesized and characterized at low solution temperatures. These complexes resemble the catalytic cores of tyrosinases, and allowed phenolate‐ligated Cu III intermediates during hydroxylation reactions to be probed, providing insights into the enzymatic mechanisms.